Becoming and Remaining an Independent Union: A Comparative Case Study of Two University Faculty Unions - Gagnon, Melanie; Beaudry, Catherine (Just Labour, 2014)
Although workplace unions have many options when it comes to affiliating with a central labour body, some unions decide to remain independent or to disaffiliate after an experience of affiliation. To our knowledge, the literature has not widely examined the reasons behind the decision of some unions to remain independent. Based on a comparative case study of two university faculty unions in Quebec, this article aims to partly fill this gap in analysis. The results show that the particularities of the work of professors and the types of expertise needed to perform their duties influence their choice for union independence.